Axisymmetric consolidation behavior of multilayered unsaturated soils with transversely isotropic permeability - Shen, Lu; Qian, Bin; Li, Liuyang (Frontiers in Earth Science, 2024)
Time-dependent consolidation behavior of unsaturated soils is a vital problem in the geotechnical engineering. With the aid of the Fredlund consolidation theory, this work further assumes the total stress of soils skeleton freely change, and extends the Fredlund consolidation theory to a Biot-type theory, establishing the fully-coupled equation model of multilayered unsaturated poroelastic media with transversely isotropic permeability. To convert the partial differential governing equation into ordinary differential equations, the integration transform technology is applied. Subsequently, the precise integration method is used to acquire the time-dependent consolidation solution of multilayered unsaturated media with transversely isotropic permeability in the transformed domain, which is further solved in the actual domain by the inverse Hankel transform. A verification examples is provided to compare the present results with the existing work in the literature, showing a great coincidence and proving the feasibility of the present solution. Finally, numerous numerical examples are presented to investigate the evolution of excess pore pressure and settlement under quasi-static loads, revealing the consolidation behavior of unsaturated soils. The results demonstrates that the ramping time, stratification, permeability, depth and m1w have a significant effect on the consolidation behavior.